Comparison of Mother’s and Toddler’s Characteristics Based On The Nutritional Status of The Toddler - Arum, Puspito; Nurmawati, Ida; Muna, Niyalatul; Muflihatin, Indah; Mudiono, Demiawan Rahmatta Putro; Wicaksono, Andri Permana (Indonesian Journal Publisher, 2023)
Nutritional status in toddlers is one of the indicators used to describe the quality of toddler health. Toddlers’ nutritional status is interpreted based on some indices, namely weight for age, length/height for age, and weight for length/height Z-score. The nutritional status of toddlers is affected by various factors, both maternal and child factors. Anaemia and chronic energy deficiency during pregnancy affect a toddler’s nutrition status. Birth weight, exclusive breastfeeding, and complementary food may result in a toddler’s nutrition status as well. This study aims to compare the mother’s and toddler’s characteristics based on the nutritional status of the toddler. This was an observational analytical cross-sectional study. All data for the analysis of this paper were obtained from observations of the toddlers, interviews with mothers, and recorded data from KIA book. Toddlers’ weight and length/height were measured when the subject came to Posyandu. Questions about exclusive breastfeeding and complementary food were asked of mothers. Information about anaemia and chronic energy deficiency status was obtained from KIA book. This study used chi-square test to finds evidence that, on 88 subjects, there is no difference in anaemia and chronic energy deficiency during pregnancy, birth weight, exclusive breastfeeding, and complementary food among all nutritional status indices.